Efektifitas Edukasi Pencegahan HIV/ AIDS Melalui Small Group Discussion Pada Remaja - Dewa Ayu Surinati; Mrs Suratiah; Dewa Made Ruspawan; Ni Nyoman Haratati; Nebgah Runiari (Jurnal Pengabmas Masyarakat Sehat, 2020)
Cases of HIV / AIDS in Indonesia are increasing rapidly, free behavior and lifestyles have made this case go fast. This is possible because of the lack of access to information obtained by adolescents relating to HIV-AIDS. The results showed knowledge of HIV and AIDS in adolescents with less categories are still quite large, which is 48.9 percent.The aim of community service is to Increase the knowledge of adolescents about HIV / AIDS in SMA The working area of the Sukawati I Gianyar Health Center, with the education method through small group discussions. (70.7%) and 29.3% level of knowledge is good and after being educated the level of knowledge of adolescents mostly becomes good (90%). The analysis showed that there were differences from 75 teenagers who had better knowledge than before, and there were differences in scores between pre-test and post-test with a value (z) of -7,588a. Wilcoxon test results of knowledge of adolescents found a significant value (p) of 0,000 can be concluded that education on HIV AIDS prevention is effective through small group discussions on adolescents. Keywords: Education, HIV / AIDS, Small Group Discussion